Responding to non-stereotypical material: a case study in Egypt - Rashad, Amira (AUC Knowledge Fountain, 2015)
Examining the effect of exposing young children to non-stereotypical material has received an increasing amount of attention. Researchers investigated how the different sources of media that young children are exposed to affect their perceptions of gender roles and gender-related characteristics. Researchers in the Arab countries have started calling for enhancing females’ representation in children’s fiction. However, little research has been conducted with the aim of investigating how young children in the Arab countries would respond to non-stereotypical material The study examines how eight-year-old Egyptian children perceive gender roles and what kind of characteristics they employ when describing males and females. Sixteen eight-year-old Egyptian children (nine boys and seven girls) responded to pictures of men and women working in non-stereotypical jobs as well as to the non-stereotypical story book entitled The Paper Bag Princess by Robert Munsch. In this study, students discussed gender roles in a whole class discussion as they responded to pictures of men and women in non-stereotypical jobs. They also reflected on the non-stereotypical story book in group discussions in which they expressed how they perceived each character, and how a typical prince and princess would act differently. The students then created princes and princesses through writing. In their written discourse, the students had the freedom to reveal how they actually perceive females and males. Students’ writings presented vivid descriptions of princesses and princes. These descriptions not only included their physical appearance, but also their actions, the activities they engaged in and the roles they undertook. The researcher adopted Fairclough’s (1995) Critical Discourse Analysis (CDA) model to analyze the students’ spoken and written discourse in relation to the social context of the Egyptian society. The researcher thoroughly analyzed students’ discourses, examined the framing and discussed how students’ perceptions of gender roles and gender-related characteristics relate to the social context of the Egyptian society. An important finding is that the change of the mean of representation from oral discussions to written descriptions resulted in different gender representations. In the whole class discussions and non-stereotypical story book group discussions, 11 students (six boys and five girls) reflected some stereotypical representations of gender roles and gender-related characteristics through speaking and writing. In the writing activity, students had more freedom to express their perceptions of gender. Six out of seven girls only presented traditional representations of the females that resembled to a great extent the typical Disney princesses. Unlike the girls, five out of nine boys presented unconventional representations of females in which princesses were engaged in non-stereotypical activities including fighting, scheming, exercising, rescuing people and working as firefighters and mechanics. There could be many possibilities to explain why boys were influenced by the non-stereotypical material they received in the study more than girls. One possibility relates to the type of the writing task that is writing about a fairytale prince and princess. This writing task may have led six girls and four boys to present stereotypical representations that match typical princes and princesses in classical Disney movies. While boys preferred to do their writing task individually, girls discussed their descriptions of their self-created princes and princesses as they write, which led six of them to have very similar writings. This act of collaboration, which is part of the discourse of femininity (Wohlwend, 2012) could present another explanation to why more boys presented their self-created princesses non-stereotypically. Exposing young children to non-stereotypical material challenges the gender stereotypes they may grow up with, and lets them understand that females and males are equally competent.